Hubungan Hubungan Tingkat Pengetahuan Orang Tua Tentang Penyakit DHF Dengan Kecukupan KebutuhTingkat Pengetahuan Orang Tua Tentang Penyakit DHF Dengan Kecukupan Kebutuhan Cairan Anak Dengan DHF di Ruang Perawatan Anak Rumah Sakit Panti Rapih Yogyakarta - Fransisca Yudita Widhiastuti; Agnes Mahayanti; Christin Ririn Widianti (STIKes Panti Rapih, 2022)
Background: Knowledge is a guide in shaping one's actions. Dengue Hemorrhagic Fever (Dengue Hemoragic Fever) is an infectious disease caused by the dengue virus which causes acute fever. Dengue fever generally goes away on its own. Supportive treatment that is given is replacement of fluids by drinking lots of water and getting plenty of bed rest. Administration of fluids is the main management of DHF patients. Purpose : The purpose of this study was to determine the relationship between the level of parental knowledge about DHF with the adequacy of meeting the water needs of children suffering from DHF in the pediatric ward at Panti Rapih Hospital. Methods: This study used a quantitative type, analytic survey design with a cross sectional approach. The population in this study were DHF patients who underwent treatment in the children's room at the Panti Rapih hospital. The sampling technique used was accidental sampling where respondents were taken DHF patients who were treated in the child care room on December 21, 2020 - January 21, 2021 with a total of 30 respondents. The research instruments used were questionnaires and assessment sheets for children's fluid needs. Results: The result of this study is that there is a significant relationship between the level of parental knowledge about DHF with the adequacy of fulfilling children's fluid needs (Pv = 0.016). Conclusion: There is a relationship between the level of parental knowledge about DHF with the adequacy of fulfilling the fluid needs of children suffering from DHF in the child care room at Panti Rapih Hospital. It is hoped that the nurses in the child care room will pay more attention to the understanding of parents about the illness suffered by patients so that they can help the healing process. Key words: knowledge of DHF, adequacy of fluids